Pengaruh Person Job Fit Terhadap Kinerja Pegawai dengan Beban Kerja Sebagai Variabel Mediasi pada Lingkup Pegawai Dinas Perumahan dan Kawasan Permukiman Kabupaten Tanjung Jabung Timur - Saputra, Dian Tirta; Amin, Shofia; Adriani, Zulfina (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to examine the effect of person-job fit on employee performance, the effect of workload on employee performance, and the effect of person-job fit on workload. In addition, this study also aims to analyze the role of workload as a mediating variable in the relationship between person-job fit and employee performance, thereby providing a more comprehensive understanding of the mechanisms influencing the improvement of employee performance within the organization. This study uses a quantitative approach with a survey method. Data were collected through the distribution of questionnaires to employees and analyzed using statistical analysis techniques based on Structural Equation Modeling (SEM). The research results show that person-job fit has a positive and significant effect on employee performance. Workload also has a positive and significant effect on employee performance. In addition, person-job fit affects workload, and workload has been proven to mediate the relationship between person-job fit and employee performance. These findings indicate that the alignment between employee competencies and job demands, as well as proper workload management, are important factors in enhancing employee performance. This study provides managerial implications for organizations in efforts to place employees in positions that match their competencies and to arrange a proportional workload.